Witold Gombrowicz w kalejdoskopie recepcji - Dimitrina Hamze (Postscriptum Polonistyczne)
Seen through the perspective of reception, the works of Witold Gombrowicz constitute a wide range of receptive proposals, selectively updated in the constant dynamic of the interactive discourse between the literary subject and the reader. The reader is invited in a covert partnership with his communication peer (the author–the producer) in their joint journey to the own polyphonic, unidentifiable, mutational ego. The relation to the self, as permanently disputed by otherness, finds its artistic application through the comic as the most powerful weapon against the Form, both in the field of the author and of the recipient.